GALEN AND HIS KNOWLEDGE IN THE FIELD OF PHARMACOLOGY - K. S. Guzev (Разработка и регистрация лекарственных средств, 2019)
The paper presents the literature data on the knowledge K. Galen in pharmacology. The source of information is the materials published in domestic and foreign literature.